Failure to achieve reduction on developmental dysplasia of hip: an ultrasound evaluation. (April 2023) - Shi, Miao; Ban, Yongguang; Luan, Qinhua; Guo, Lingfei; Wang, Yanzhou; Li, Tianyou; Zhao, Qinghua; Pan, Xiaojie; Li, Xin; Teng, Jianbo
Background: Ultrasound examination of the medial side of the hip joint has been rarely used to evaluate the status of developmental dysplasia of the hip (DDH) in Pavlik harness treatment according to the literature. Purpose: To analyze the effects of cartilaginous acetabulum, hip joint labrum, and acetabular tissue on the reduction of DDH. Material and Methods: A total of 50 cases (100 hips) were detected by the Graf method with a high-frequency linear transducer (L 5–12), and there were 59 dislocated hips and 41 non-dislocated hips. Patients were treated with a Pavlik harness. Ultrasound examination of the medial side of the hip joint was performed for follow-up. The hip joints were divided into three groups: the non-dislocated group; the reducible group; and the non-reducible group. Results: The success rate of reduction was significantly higher when the acetabulum cartilage was located on the cephalic side (chi-square = 28.12, P  < 0.001). The success rate was also significantly higher when the hip joint labrum was located on the cephalic side (chi-square = 17.21, P  < 0.001). Type III and D had a higher success rate of reduction than type IV ( P  < 0.001). The pairwise comparison of the measurements of acetabular tissue between the non-dislocated group, the reducible group, and the non-reducible group showed statistical differences ( P  < 0.001). Conclusion: The present study confirmed that the location of acetabulum cartilage and hip joint labrum affected the outcome of treatment. The degree of dislocation and the amount of acetabular tissue were correlated with the success rate of treatment.